SOSIALISASI PERAN SDM DALAM MENINGKATKAN EFISIENSI PENGELOLAAN ANGGARAN DI UMKM CENGKEH DESA CIWINDU KAB. SERANG - Harry Triana; Ani Apriani; Cokorda Agung Wibowo (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
The Community Service activity was conducted on October 3-4, 2024, in Ciwindu Village, Serang Regency, with the theme “The Role of Human Resources in Enhancing Budget Management Efficiency in Cengkeh SMEs.” This program aimed to increase SME actors' understanding of the importance of strategic HR management to support budget efficiency. The methods used included interactive presentations, group discussions, and case simulations, focusing on budget planning efficiency and the use of simple technology for financial recording. The results showed an increase in SMEs' awareness of effective budget management and team collaboration. This activity is expected to have a sustainable impact on improving the HR capacity of SMEs in Ciwindu Village. Keywords: Human Resources; Budget Management; SMEs